Development of sustainable tourism in Ukraine - Marshalenko, Marianna (My University, 2018)
Issues of sustainable tourism in Ukraine are disclosed.
Keywords: туризм; сталий туризм; Україна; кафедра туристичного та готельного бізнесу; устойчивый туризм; Украина; tourism; sustainable tourism; Ukraine